2014
DOI: 10.12691/ajmsm-2-5-4
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Pathological Correlation Study of Leprosy in a Tertiary Care Teaching Institute in Northwest Punjab, India

Abstract: Background: Leprosy continues to be a predominant public health problem in India despite rapid strides made for its prevention, detection and treatment since ages. As leprosy can occur in any form due to immunological status of the patient, its clinico-pathological correlation gains more importance. Aim: The present research was undertaken to ascertain the importance of skin biopsy in detecting and diagnosing difficult cases where clinical diagnosis alone is not sufficient and a clinico-pathological correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
5
6
2
Order By: Relevance
“…In the present study, majority of the patients were of PB type (32 cases; 51.61%) and the rest were of MB type (30 cases; 48.38%) on tissue sections. Similar observations were made by Badhan R et al [7] while study done by Giridhar et al 11 showed majority of patients were of MB type (55 cases; 56.13%). The bacterial index on SSS was calculated in 52 cases, out of which 17 cases (32.69%) were positive for acid fast bacilli [ Table 4].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, majority of the patients were of PB type (32 cases; 51.61%) and the rest were of MB type (30 cases; 48.38%) on tissue sections. Similar observations were made by Badhan R et al [7] while study done by Giridhar et al 11 showed majority of patients were of MB type (55 cases; 56.13%). The bacterial index on SSS was calculated in 52 cases, out of which 17 cases (32.69%) were positive for acid fast bacilli [ Table 4].…”
Section: Discussionsupporting
confidence: 85%
“…Histopathologically, the most commonly encountered type of leprosy was IL (21 cases; 33.90%), followed by LL (16 cases; 25.80%) and the least common type was the BB (1 cases; 1.61%).Similar observations were made by Singh J et al [5] and Arunagirinathan M et al, [6] while BT was the most common type in the study done by Badhan R et al [7] and Rizvi A A et al [8] The high percentage of IL noted histopathologically in our study could have been due to immunological differences in host responses, duration of the lesion, nature and depth of the biopsy, quality of the sections and number of acid fast stained sections examined. Selection of the site of biopsy also plays an important role since clinically different lesion biopsied from same patient can show different type of histopathology.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the studies showed the peak incidence in 21 to 30 years and 21 to 40 years. Hence the minimum number of cases observed in the present study was in the 1st decade and it is in full agreement with Fauziahkurdi et al, 15 Tekwani D and Joshi R et al 11 In the present study our observation for distribution of leprosy cases in both sexes is in concordance with other studies like, Fakeha Firdous DP et al, 16 Kumar A et al, 17 Badhan R et al, 18 Mehta. B et al, 19 Premanshu Bhushan et al, 20 Veena Shivamurthy et al 21 In the present study our observations shows that 57/80 i.e.…”
Section: Subject Characteristicssupporting
confidence: 93%
“…Histological diagnosis was established in 92.3 % cases in the present study by two pathologists, which is similar to other studies in literature. [17] The overall clinicopathological correlation in our study was 66.7% i.e. there was complete agreement between clinical and histopathological diagnosis in 40 cases.…”
Section: Discussionsupporting
confidence: 64%